2020
DOI: 10.36899/japs.2020.1.0025
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and in Vitro Investigation of Anti-Inflammatory and Xanthine Oxidase Inhibition Potential of Root Extracts of Bryophyllum Pinnatum

Abstract: The aim of present study is to emphasize the phytochemical and biological studies of root extracts of Bryophyllum pinnatum, as little work was documented on the roots. Phytochemical analysis of powder and extracts were evaluated by the standard methods. UV/ Visible scanning, FTIR and atomic absorption spectroscopy were also performed for the purposes of standardization. In vitro anti-inflammatory investigation was done by protein denaturation method and xanthine oxidase inhibition assay was performed to confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…A count of 187 (73.6%) participants reported their satisfaction with the results of traditional medicine. Traditional medicine has been excessively used with almost no threats to health as this stands consistent with various studies 31,32 . In a previous study, people have reported a positive response to traditional medicine use, however, few people also showing reservations regarding its use.…”
Section: Figure 6 Responses Among Universities About Commonly Use Med...supporting
confidence: 76%
“…A count of 187 (73.6%) participants reported their satisfaction with the results of traditional medicine. Traditional medicine has been excessively used with almost no threats to health as this stands consistent with various studies 31,32 . In a previous study, people have reported a positive response to traditional medicine use, however, few people also showing reservations regarding its use.…”
Section: Figure 6 Responses Among Universities About Commonly Use Med...supporting
confidence: 76%
“…1,23,24 The presence of glycosaponins in the plant has indicated that C. oblongapossesses antitussive, anti-diabetic and antimicrobial properties as many previous scientific reports have documented the beneficial effects of glycosaponins. 25 Glutathione-S-transferases (GSTs) are a diverse family of Phase II detoxification intracellular enzymes. Cytosolic GSTs play a crucial role in regulating the mitogen-activated protein (MAP) kinase pathway that participates in cell survival and death signals.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous root extract has been reported to be active as an anti-inflammatory agent in an in vitro investigation using a protein denaturation method, with an IC 50 value of 570.24 μg/mL. 34 Single topical application of the ethanol extract inhibited mice ear edema induced by croton oil (57%, inhibition), arachidonic acid (67%, inhibition), phenol (80%, inhibition), capsaicin (72%, inhibition), and EPP (75%, inhibition). 291 The methanolic extract of the leaves has also been reported to inhibit formaldehyde-induced paw edema in rats.…”
Section: Amentioning
confidence: 99%